2022
DOI: 10.1590/1808-057x202113080
|View full text |Cite
|
Sign up to set email alerts
|

Informational content of key audit matters and financial analysts’ forecasts

Abstract: The aim of this article was to analyze the relationship between the informational content of the key audit matters (KAMs) reported in the Independent Audit Report (IAR) and financial analysts’ forecasts for the companies listed on the B3 S.A. - Brasil, Bolsa, Balcão (B3). The research that has investigated the relevance of KAMs has not analyzed the incremental information about the audited firm, from the independent auditor’s viewpoint, that can affect financial analysts’ forecasts. The findings of this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
4
0
5
Order By: Relevance
“…Audit expectation gap; creditors’ benefits and perceptions; investors’ reactions and perceptions; and financial analysts’ forecasts and perceptions are variables that form the third group of EAR consequences, i.e. auditee-stakeholder relationship (Hatherly et al , 1991; Innes et al , 1997; Liu et al , 2022; Rapley et al , 2021; Gutierrez et al , 2018; Venturini et al , 2022; Hu et al , 2022). Following the agency, stakeholders and legitimacy theories, some results of these studies imply that improving the audit report transparency through EAR can reduce the expectations gap, information asymmetry and possible conflicts of interest between management and shareholders and increase the stakeholders’ trust and the company’s legitimacy (Suttipun, 2022; Fuller, 2015).…”
Section: Results Of Content Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Audit expectation gap; creditors’ benefits and perceptions; investors’ reactions and perceptions; and financial analysts’ forecasts and perceptions are variables that form the third group of EAR consequences, i.e. auditee-stakeholder relationship (Hatherly et al , 1991; Innes et al , 1997; Liu et al , 2022; Rapley et al , 2021; Gutierrez et al , 2018; Venturini et al , 2022; Hu et al , 2022). Following the agency, stakeholders and legitimacy theories, some results of these studies imply that improving the audit report transparency through EAR can reduce the expectations gap, information asymmetry and possible conflicts of interest between management and shareholders and increase the stakeholders’ trust and the company’s legitimacy (Suttipun, 2022; Fuller, 2015).…”
Section: Results Of Content Analysismentioning
confidence: 99%
“…increasing the readability and quality of audit reports (Smith, 2023;Li et al, 2019) and providing relevant information for stakeholders' decision-making (Alves Júnior and Galdi, 2019;Tiron-Tudor et al, 2018;Sneller et al, 2017;Prasad and Chand, 2017;Christensen et al, 2014;Cordos and Fülöp, 2015). Other research showed the essential impact of EAR on the accuracy and dispersion of analyst forecasts (Hu et al, 2022;Venturini et al, 2022), reduced management misbehaviors (Klueber et al, 2018); improving financial quality (Reid et al, 2019). Finally, Gimbar et al (2016aGimbar et al ( , 2016b argue that EAR increases the auditor's responsibility which may lead auditors to improve the audit procedures to minimize the audit risk.…”
Section: Articles Published Between 2013 and 2022mentioning
confidence: 99%
“…This technique consists of trimming the extreme values (above or below the defined minimum and maximum percentiles), replaced by the lowest and highest values remaining in the distribution, calculated by the selected percentiles. In this study, winsorization was performed at the 1% level, in line with the survey by Venturini et al (2022). With winsorization, the mean EPS become clearer (free of outliers) and allow the results to verify whether there is any difference between analyzing EPS by the mean or by the median.…”
Section: Methodsmentioning
confidence: 99%
“…Brown et al and Kross et al found that the advantage of analyst forecasts is related to the length of time between the last financial report of a listed company and the current forecast of the securities analyst [2][3][4]. Venturini et al also find that from an independent audit perspective, the higher the value of information on key audit matters the more it reduces the error rate of analysts' forecasts [5].…”
Section: Lliterature Reviewmentioning
confidence: 99%